Behaviour of thin-walled castellated beams strengthened using CFRP. (April 2021) - Cyril Thomas, A.; Baskar, K.
Abstract: This paper presents the behavior of Carbon Fibre Reinforced Polymer (CFRP) strengthened Thin-Walled Castellated Beams (TCBs). A detailed experimental study was carried out in two phases viz, 1. Study on effective bonding between steel substrate and CFRP under varying surface preparation scales, 2. Ultimate load behavior of TCBs provided with and without CFRP strengthening. While studying the effect of bonding between steel substrate and CFRP under various surface preparation, the bond strength of specimens prepared with copper-slag blasting was potentially stronger due to the maximum ultimate direct tensile stress of 2.54 N/mm 2 in pull-off test. The investigation on ultimate load behavior of TCBs provided with and without CFRP strengthening was carried out experimentally on ten beams under the domination of Shear (SDB), Moment (MDB) and Moment & Shear (MSDB). This strengthening process was more effective in MDBs. Especially the load carrying capacity was increased by 35.38% in plastic section and 42.53% in semi-compact section and significant ductility enhancement observed in MDBs. Simultaneous interaction between shear and bending mode of failure of TCBs were studied.